2014
DOI: 10.1111/epi.12654
|View full text |Cite
|
Sign up to set email alerts
|

USL255 extended‐release topiramate: Dose‐proportional pharmacokinetics and tolerability in healthy volunteers

Abstract: ObjectiveEvaluate the pharmacokinetics (PK), safety, and tolerability of single doses of once-daily USL255, Qudexy XR (topiramate) extended-release capsules, over a wide dosing range.MethodsTwo single-dose, phase I studies in healthy adults were used to evaluate the PK profile and maximum tolerated dose (MTD) of USL255 from 25–1,400 mg. Standard PK parameters assessed included area under the plasma concentration-time curve (AUC) and maximum plasma concentration (Cmax). Dose proportionality, linearity, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The most common TEAEs in either treatment group were nausea, paresthesia, dizziness, and headache, and all TEAEs were mild or moderate in intensity. These adverse events were not unexpected for topiramate and have been observed in previous studies of USL255, both in healthy participants and in patients with epilepsy [9][10][11]14,17].…”
Section: Bioequivalence Of Usl255 Beads Sprinkled Onto Applesauce Versupporting
confidence: 82%
See 1 more Smart Citation
“…The most common TEAEs in either treatment group were nausea, paresthesia, dizziness, and headache, and all TEAEs were mild or moderate in intensity. These adverse events were not unexpected for topiramate and have been observed in previous studies of USL255, both in healthy participants and in patients with epilepsy [9][10][11]14,17].…”
Section: Bioequivalence Of Usl255 Beads Sprinkled Onto Applesauce Versupporting
confidence: 82%
“…USL255, Qudexy® XR (topiramate) extended-release capsules (Upsher-Smith Laboratories, Maple Grove, MN, U.S.A.), is a once-daily, XR formulation of topiramate-a broad-spectrum, well-established AED-available as 25-mg, 50-mg, 100-mg, 150-mg, and 200-mg capsules. In previous phase 1 studies, USL255 displayed dose proportional pharmacokinetics (PK) [9] and, compared with immediate-release topiramate dosed twice daily, provided equivalent topiramate exposure with a 26% decreased fluctuation index at steady state [10]. A placebocontrolled, randomized, multinational phase 3 study found that USL255 200 mg was efficacious and generally well tolerated in the adjunctive treatment of partial-onset seizures (POS) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…47 Metabolic acidosis and kidney stones were not reported in patients in this study. 33,47,48 In an article that summarized phase I QXR data from 2 studies (25-400 and 600-1400 mg/day), the incidence of nausea in healthy volunteers was 0% in the placebo group; it was 17% (5 of 30) and 12% (5 of 40) for the lower and higher treatment ranges, respectively. Furthermore, there was a dose-dependent incremental reporting of TEAEs (11% for 25 mg, 46% for 400 mg, and 92% in study subjects who received doses of 600-1400 mg).…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…TPM-IR is approved in many countries as an adjunctive treatment for patients with partial-onset seizures or primary generalized tonic–clonic seizures. USL255 is an extended release topiramate (TPM-XR) formulation that was developed to deliver consistent drug release over a 24 h dosing interval [33] . A double-blind, randomized, placebo controlled PREVAIL Phase III clinical study ( Table 1 ) demonstrated that once-daily administration of USL255 is an effective adjunctive therapy for reducing the seizure frequency in patients with refractory partial onset seizures [32] .…”
Section: Antiepileptic Drugs Under Clinical Developmentmentioning
confidence: 99%